2021
DOI: 10.1002/cnr2.1407
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid expansion and insurance status, cancer stage, treatment and mortality among patients with cervical cancer

Abstract: Background: Currently, little is known about the effect of the Patient Protection and Affordable Care Act's Medicaid expansion on care delivery and outcomes in cervical cancer.Aim: We evaluated whether Medicaid expansion was associated with changes in insurance status, stage at diagnosis, timely treatment, and survival outcomes in cervical cancer.Methods and results: Using the National Cancer Database, we performed a difference-in-differences (DID) cross-sectional analysis to compare insurance status, stage at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…As Snyder and colleagues suggest, these findings lend support for the role Medicaid expansion has in improving cancer diagnosis, care, and outcomes, corroborating prior studies 8, 13, 34 . Work using data from patients who receive treatment at community health centers (CHCs), which provide primary care for people who are underserved regardless of insurance status, 35 lends insight into how decreasing barriers to care for people who lack insurance can improve access to cancer screening.…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 53%
See 1 more Smart Citation
“…As Snyder and colleagues suggest, these findings lend support for the role Medicaid expansion has in improving cancer diagnosis, care, and outcomes, corroborating prior studies 8, 13, 34 . Work using data from patients who receive treatment at community health centers (CHCs), which provide primary care for people who are underserved regardless of insurance status, 35 lends insight into how decreasing barriers to care for people who lack insurance can improve access to cancer screening.…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 53%
“…As Snyder and colleagues suggest, these findings lend support for the role Medicaid expansion has in improving cancer diagnosis, care, and outcomes, corroborating prior studies. 8,13,34 Work using data from patients who receive treatment at community health centers (CHCs), which provide primary care for people who are underserved regardless of insurance status, 35 lends insight into how decreasing barriers to care for people who lack insurance can improve access to cancer screening. One study found that in the CHC setting wherein health insurance is not a barrier to care, rates of colorectal and cervical cancer screening increased after implementation of the ACA; the same study found that in the CHC setting, rates of cervical cancer screening increased the most among Black patients in MES.…”
mentioning
confidence: 99%
“…Several studies have similarly utilized the NCDB to measure changes in insurance and stage at presentation following Medicaid expansion, most finding measurable increases in insurance coverage and modest effects cancer stage, concordant with the findings of this study and suggestive of the need for longer follow-up to identify measurable change. [6][7][8][9] One early study examined changes in stage at diagnosis over time for 17 common cancer types based on Medicaid expansion status and identified subtle shifts towards presentation with stage I disease in colorectal, lung, and breast cancer in expansion vs. nonexpansion states from 2011-2014. However, these were not significant on adjusted DID analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although six states expanded in 2010, most participating states initiated Medicaid expansion in January 2014. A number of studies have demonstrated improved rates of colorectal, breast, cervical, and prostate cancer screening among patients residing in expansion states, suggesting evidence of the intended benefit of Medicaid expansion 1‐6 . Several early studies have also reported an increased percentage of early stage disease among patients residing in Medicaid expansion states and diagnosed with breast, colorectal (CRC), head and neck, and lung cancer 7‐9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation